Impact assessment: Eroding benefits through streamlining? - Bond, A.; Pope, Jennifer; Morrison-Saunders, A.; Retief, F.; Gunn, J. (Elsevier Inc., 2014)
This paper argues that Governments have sought to streamline impact assessment in recent years (defined as the last five years) to counter concerns over the costs and potential for delays to economic development. We hypothesise that this has had some adverse consequences on the benefits that subsequently accrue from the assessments. This hypothesis is tested using a framework developed from arguments for the benefits brought by Environmental Impact Assessment made in 1982 in the face of the UK Government opposition to its implementation in a time of economic recession. The particular benefits investigated are ‘consistency and fairness’, ‘early warning’, ‘environment and development’, and ‘public involvement’. Canada, South Africa, the United Kingdom and Western Australia are the jurisdictions tested using this framework. The conclusions indicate that significant streamlining has been undertaken which has had direct adverse effects on some of the benefits that impact assessment should deliver, particularly in Canada and the UK. The research has not examined whether streamlining has had implications for the effectiveness of impact assessment, but the causal link between streamlining and benefits does sound warning bells that merit further investigation.